2020
DOI: 10.1162/opmi_a_00037
|View full text |Cite
|
Sign up to set email alerts
|

Grouping Mechanisms in Numerosity Perception

Abstract: Enumeration of a dot array is faster and easier if the items form recognizable subgroups. This phenomenon, which has been termed “groupitizing,” appears in children after one year of formal education and correlates with arithmetic abilities. We formulated and tested the hypothesis that groupitizing reflects an ability to sidestep counting by using arithmetic shortcuts, for instance, using the grouping structure to add or multiply rather than just count. Three groups of students with different levels of familia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 36 publications
3
48
0
Order By: Relevance
“…Starkey and McCandliss (2014) found that groupitizing was positively associated with children's arithmetic abilities, an association also shown in adults (Anobile et al, 2020;Ciccione & Dehane, 2020;. Proposed mechanisms for the association between groupitizing and arithmetic abilities include the extension of the subitizing range through arithmetic abilities , the use of fast repeated addition (Wender & Rothkegel, 2000), conceptual knowledge about the composition of large numbers from small numbers (Starkey & McCandliss, 2014, Clements & Sarama, 2009, Wästerlid, 2020 and the use of mental multiplication (Ciccione & Dehaene, 2020). All of these proposed mechanisms concern how numerical information is used to quickly enumerate the total number of items in the array.…”
Section: Parallel Subitizing In Grouped Arrays 16mentioning
confidence: 97%
See 4 more Smart Citations
“…Starkey and McCandliss (2014) found that groupitizing was positively associated with children's arithmetic abilities, an association also shown in adults (Anobile et al, 2020;Ciccione & Dehane, 2020;. Proposed mechanisms for the association between groupitizing and arithmetic abilities include the extension of the subitizing range through arithmetic abilities , the use of fast repeated addition (Wender & Rothkegel, 2000), conceptual knowledge about the composition of large numbers from small numbers (Starkey & McCandliss, 2014, Clements & Sarama, 2009, Wästerlid, 2020 and the use of mental multiplication (Ciccione & Dehaene, 2020). All of these proposed mechanisms concern how numerical information is used to quickly enumerate the total number of items in the array.…”
Section: Parallel Subitizing In Grouped Arrays 16mentioning
confidence: 97%
“…Our findings suggest the likely reason is that this particular way of visual grouping supports parallel subitizing of dots and groups, which in turn provides operands for mental calculations. The groupitizing effect can also be found if arrays are grouped by temporal proximity or separated colors , Ciccione & Dehaene, 2020, but seems to be heavily impaired when items are grouped by shape or color, but interspersed (Liu, Zheng, Huang & Cicchini, 2020).…”
Section: Parallel Subitizing In Grouped Arrays 16mentioning
confidence: 99%
See 3 more Smart Citations